1970
DOI: 10.3329/jbsp.v2i0.978
|View full text |Cite
|
Sign up to set email alerts
|

Serum Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) Levels in Different Grades of Protein Energy Malnutrition

Abstract: The present study was designed to analyze serum AST, ALT levels in different grades of protein energy malnutrition to facilitate early diagnosis, management and rehabilitation of PEM. The serum AST and ALT levels of 50 children of aged 5months to 5 years of both sexes were studied. Among them, 30 children suffering from protein energy malnutrition of 3 different grades were selected for experimental group. Age and sex matched 20 apparently healthy children with no systemic disorder and with weight/height rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
2
8
0
2
Order By: Relevance
“…SGOT and SGPT level in this study were higher in patients with malnutrition compared to control group, but both were still with in normal range. This was consistent with study was done by Chrowdury et al which obtained a result that there was an increase of SGOT and SGPT in patients with malnutrition [20]. In this study, the samples were limited to patients with normal hepatic function marked by normal SGOT and SGPT value.…”
Section: Discussionsupporting
confidence: 91%
“…SGOT and SGPT level in this study were higher in patients with malnutrition compared to control group, but both were still with in normal range. This was consistent with study was done by Chrowdury et al which obtained a result that there was an increase of SGOT and SGPT in patients with malnutrition [20]. In this study, the samples were limited to patients with normal hepatic function marked by normal SGOT and SGPT value.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Hyder et al (2013) explain that the levels of AST and ALT increased on condition of viral hepatitis infection, alcohol use, and cirrhosis of the liver [28]. While the research conducted by Crawdury et al (2007) get different results, which found elevated levels of AST and ALT in marasmic malnutrition patients [29]. In this research that we had excluded patients with liver disease and autoimmune diseases, so there were no differences between the two of groups.…”
Section: Resultsmentioning
confidence: 84%
“…This may lead to deposit of more lipids in liver and help the formation of fatty liver. An increased level of ALT and AST in serum in low dietary protein fed rats was due to enhance transamination to metabolize the excess amino acids release from tissue breakdown to compensate low dietary protein 22 . Significantly increased levels of serum ALT and AST in all the excess vitamin A supplemented rats is due to toxic effects of vitamin A on liver 23 .…”
Section: Discussionmentioning
confidence: 99%